Effect of mixing events on the production of a thermo-tolerant and acid-stable phytase in a novel solid-state fermentation bioreactor. (October 2017) - Arora, Sidharth; Dubey, Mayank; Singh, Pritam; Rani, Richa; Ghosh, Sanjoy
Graphical abstract: Highlights: A novel bioreactor design for solid-state fermentation. Tensile strength of hyphal bonds of Rhizopus oryzae estimated to yield optimum mixing intensity. Superior performance than tray and packed bed bioreactor for phytase production. Effect of mixing time on bioreactor performance was evaluated. Abstract: Mixing constitutes a critical design parameter in solid-state fermentation (SSF) bioreactor and its effect on heat and water transport, and microbial growth in substrate bed can significantly influence overall productivity. Effect of mixing events on the production of a thermo-tolerant and acid stable phytase, by Rhizopus oryzae, was studied in a novel SSF bioreactor, using optimized growth medium containing wheat bran and linseed oil cake (1:1) as main substrate. A critical mixing phase was identified, in the absence of which fungal growth led to the onset of heat accumulation and subsequent bed drying. The tensile strength of hyphal bonds between two substrate particles, at this critical phase, was estimated and related to the mixing intensity in the bioreactor that resulted in an optimum working value of 15 rpm. Effect of mixing time on bioreactor performance was also investigated where a 3 min mixing duration, at every 6 h, increased biomass and phytase productivity to 2.2- and 4.5-fold, respectively, in comparison to packed bed bioreactor (PBR). The proposed bioreactor system with intermittent mixing gave superior performance than PBR and tray bioreactor, in terms of maximum bed temperature, axial bed temperature and biomass gradient, average bed moisture content, biomass and phytase productivity.